a) 2x - 3 = 15;
6) (x+3)(3x – 7) = 0;
B) 3,12x + = -0,412--0,9x​
Ответ
0 (0 оценок)
1
ntv2009 1 год назад
Светило науки - 8 ответов - 0 раз оказано помощи

Ответ:

1)X=15+3

X= 18

X=18:2

X=9

Ответ
0 (0 оценок)
0
fortunatusagent008 1 год назад
Светило науки - 569 ответов - 0 раз оказано помощи

Покрокове пояснення:

2x - 3 = 15

2x = 15 + 3

2x =18

x =18:2

x =9

(x + 3)(3x - 7) = 0

x + 3 = 0            3x - 7 = 0

x = -3                3x  = 7

                          x = 2 1/3

А что за условие в третьем уравнении ?